Development of Integrated Thatic Teaching Materials Based on Discovery Learning Models in Basic Class IV - B, Hanida; S, Neviyarni (International Journal of Educational Dynamics, 2019)
This research is a type of development research which in English is called Research and Development (R & D). This study uses a 4D model (four-D models). The subjects to be tested on the development of integrated thematic teaching materials on theme 7 are grade IV elementary school. This study aims to produce new products through certain stages, so as to produce products that are tested for validity and practicality, and effectiveness and to develop and produce a product in the form of teaching materials to overcome classroom problems and not as theory testers.. Keywords: Teaching Materials, Integrated Thematics, Discovery Learning